Incentives, Productivity, and Labor Contracts - Lazear, Edward P.; Moore, Robert L. (Quarterly Journal of Economics, 1984)
The relationship between age-earnings profiles and worker incentives is examined by contrasting wage and salary workers with the self-employed. It is argued that the steepness of wage and salary workers' age-earnings profiles reflects the desire to provide work incentives to those workers. Since self-employed workers do not face this agency problem, they are used as a benchmark to gauge productivity. Empirical support of the proposition is provided, and the effects of human capital accumulation are separated empirically from incentive effects. The most important conclusion is that under some strong assumptions, most of the slope in age-earnings profiles is accounted for by the desire to provide incentives, rather than by on-the-job training.